Burn : a novel - Heller, Peter, 1959- (Alfred A. Knopf, 2024)
"Every year Jess and Storey have made an annual pilgrimage to northern Maine where they camp, hunt, and hike, leaving much from their long friendship unspoken. Although the state has convulsed all summer with secession mania--a mania that had simultaneously spread across other states--Jess and Storey figure it's a fight reserved for legislators or, worse-case scenario, folks in the capitol. But after two weeks hunting moose off the grid, the men reach a small town and are shocked to find a bridge blown apart, buildings burned to the ground, and bombed-out cars abandoned on the road. Trying to make sense of the sudden destruction all around them, the men set their sights on finding their way home, dragging a wagon across bumpy dirt roads, ransacking boats left in the lakes, and dodging men who are armed--secessionists or military, they cannot tell--as they seek a path to safety. And then, a startling discovery, a child in the cabin of a boat, drastically alters their path and the stakes of their escape."--